2019
DOI: 10.1109/access.2019.2898180
|View full text |Cite
|
Sign up to set email alerts
|

Secure On-Off Transmission in mmWave Systems With Randomly Distributed Eavesdroppers

Abstract: To meet ever-increasing mobile data traffic demands for next-generation wireless communication systems, the plentiful spectrum resources in millimeter wave (mmWave) band have been exploited to improve the system capacity. This paper investigates physical layer security of mmWave systems with different secure on-off transmission strategies in the presence of randomly distributed eavesdroppers, including capacity threshold-based on-off scheme, secrecy guard zone on-off scheme and hybrid on-off scheme. Considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…This assumption applies to networks that combine broadcast and multicast transmissions when the eavesdroppers are active [25], [40], [41]. Furthermore, even for a passive eavesdropper, recent studies have shown that we can still detect the presence of passive eavesdroppers by unintentionally leaking local oscillator power from the radio frequency frontend of the eavesdropper receiver [42].…”
Section: B Directional Beamformingmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption applies to networks that combine broadcast and multicast transmissions when the eavesdroppers are active [25], [40], [41]. Furthermore, even for a passive eavesdropper, recent studies have shown that we can still detect the presence of passive eavesdroppers by unintentionally leaking local oscillator power from the radio frequency frontend of the eavesdropper receiver [42].…”
Section: B Directional Beamformingmentioning
confidence: 99%
“…Moreover, for mathematical tractability, it makes sense to approximate the antenna pattern with a sectorial model when simple maximum signal-to-noise ratio beam steering is assumed, where constant directional gains are assumed for both main lobe and side lobe [24]. By using a sectored antenna model, PLS of mmWave systems with different secure on-off transmission strategies in the presence of randomly distributed eavesdroppers was studied in [25]. The work in [20] investigated the secrecy performance of the noise-limited and the AN-assisted mmWave networks.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [20], we have considered an UAV-enabled mmWave communication system, in which a source transmits the signals to a destination via a determined UAV relay, physical-layer security has been studied by using the 3D directional antenna pattern. It is worth mentioning that the on-off transmission [21,22], as an effective measure to guarantee the transmission quality and further enhance physical-layer security, still has not been investigated in UAV relay networks.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Based on the above system model, there are multiple ground eavesdroppers monitoring the transmission of R 0 → D link and attempting to interpret the confidential messages. In order to enhance physical-layer security, the on-off transmission scheme is adopted at R 0 , as done in [21,22]. More specifically, based on the pilot signals from D, R 0 can obtain the channel capacity C R 0 D of the R 0 → D link.…”
Section: Relay Selection and Transmission Schemementioning
confidence: 99%
“…The main idea of PLS is to make use of the normal randomness of wireless communication channel to guarantee that the confidential information is transferred to the legitimate receiver and that the confidential information will not be decoded by illegal users [6][7][8][9][10]. Reference [11] provided a detailed, transparent and accurate information on the latest developments in the use of collaborative techniques to improve PLS.…”
Section: Introductionmentioning
confidence: 99%